"The early days" – underwater prehistoric archaeology in the USA and Canada. (10th August 2020) - Garrison, Ervan G.; Cook Hale, Jessica W.
Abstract: Here, we present a historical review of important published studies of submerged prehistoric sites in North America prior to 1990. Prior to that point, a review of mid-twentieth century literature on the subdiscipline demonstrates that "prehistoric" was not a significant element in practice. In the U.S.A. and Canada, very few professional papers or articles were published on the topic of submerged prehistoric archaeological sites until mid-century or later. Most early studies were written by avocational archaeologists or specialists from other disciplines interested in archaeology. This changed in the 1970s, when formal surveys, reports, and publications written by academically trained archaeologists increasingly appeared in peer-reviewed journals and edited volumes. By the 1980s the establishment of underwater prehistoric archaeology as new sub-discipline was well underway. This review is designed to give the reader a brief overview of the discipline as it matured, though we lack the space to provide a full critical analysis here.